Implementasi Program Sekolah Rakyat di Kota Bengkulu: Analisis Fiskal, Sosial, dan Pendidikan - Wardana, Mohamad Irfan Surya; Ismail, Ismail; Mursalin, Imam Abdurrahman; Sautomo, Sabar; Khairani, Amelia (WELFARE Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the implementation of the People's School (Sekolah Rakyat, SR) Program in Bengkulu City, which is an educational initiative with a boarding school model targeting poor and extremely poor communities. The research applies a descriptive qualitative approach by supporting primary data from student surveys and secondary data from official government documents, the Regional Fiscal Study (Kajian Fiskal Regional, KFR), and statistics from the Central Bureau of Statistics (BPS). The findings indicate that the SR Program in Bengkulu has successfully enhanced students’ learning motivation, academic performance, discipline, and self-confidence, while also reducing the financial burden on their families. Large-scale fiscal investments through state budget allocation and direct assistance to students have generated positive impacts in both educational and socio-economic domains. However, major challenges include dependence on the state budget (APBN), limited availability of qualified teachers, disparities in general educational infrastructure, and insufficient socialization in remote areas. Penelitian ini bertujuan untuk menganalisis implementasi Program Sekolah Rakyat (SR) di Kota Bengkulu, yang merupakan inisiatif pendidikan berbasis asrama untuk masyarakat miskin dan miskin ekstrem. Pendekatan penelitian menggunakan metode kualitatif deskriptif dengan dukungan data primer dari survei kepada siswa serta data sekunder dari dokumen resmi pemerintah, laporan Kajian Fiskal Regional (KFR), dan data Badan Pusat Statistik (BPS). Hasil penelitian menunjukkan bahwa Program SR di Bengkulu berhasil meningkatkan motivasi belajar, prestasi akademik, disiplin, dan rasa percaya diri siswa, serta meringankan beban ekonomi keluarga. Investasi fiskal yang besar melalui alokasi APBN dan bantuan langsung kepada siswa telah memberikan dampak positif, baik di bidang pendidikan maupun sosial-ekonomi. Namun, tantangan utama meliputi ketergantungan pada APBN, keterbatasan tenaga pendidik berkualitas, kesenjangan infrastruktur pendidikan umum, serta keterbatasan sosialisasi di daerah terpencil.